Credit relaxation Policy Affected by Covid-19 at Bank BRI Nogotirto Unit - Muhammad Jauhar Shiddiq; Danang Wahyu Muhammad (Faculty of Law, University of Mataram, 2021)
This research purpose to determine the implementation of relaxation policies based on POJK No.II / POJK.03/2020 and to examine the apply the precautionary principle (prudential principal) after the issuance of POJK No.II/POJK.03/2020 on Bank BRI Nogotirto Unit. This is using empirical juridical method with qualitative analysis then inductive-veriﬁcation testing is carried out on the latest facts contained in societyThe results of this show indicate that the implementation of the relaxation policy at the BRI Nogotirto Unit is in accordance with POJK No.II/POJK.03/ concerning 2020 National Economic Stimulus related to the requirements and procedures for applying for credit restructuring, namely the the debtor is experiencing payment diﬃculties (principal and/ or interest on credit), the debtor has good business prospects, shows good faith and is willing to fulﬁll credit obligations after restructuring. The implementation of the bank’s prudential principle (prudential principal) after the POJK was enforced at the Bank BRI Nogotirto uinit by mapping the affected customers according to the categories regulated by POJK, carrying out a restructuring scheme based on the decrease in turnover due to Covid-19, conducting debtor survival assessment, application of 5C principles are Character, Capacity, Capital, Collateral and Economic Condition of as well as based on the principles of objectivity, independence, avoiding confiicts of interest, and fairness in implementing credit restructuring at Bank BRI Nogotirto.